IMPLEMENTASI UNDANG UNDANG NOMOR 35 TAHUN 2014 TENTANG PERLINDUNGAN ANAK DI PONDOK PESANTREN AL FATTAHIYYAH TULUNGAGUNG - Ahmad Denil Muhtar; Mohammad Hasib (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The prevalence of violence against children within educational institutions, including Islamic boarding schools (pesantren), has emerged as a serious concern in the enforcement of child protection law in Indonesia. Law Number 35 of 2014 on Child Protection explicitly prohibits all forms of physical and psychological violence against children; however, its implementation in salafiyah pesantren continues to face significant challenges due to deeply rooted disciplinary traditions embodied in the practice of ta’zir. The persistent gap between positive legal norms and traditional educational practices constitutes an academic urgency that remains insufficiently explored. This study aims to describe the implementation of child protection within ta’zir practices and to analyze the supporting and inhibiting factors at Pondok Pesantren Al Fattahiyyah Tulungagung. The research employed a qualitative descriptive approach, with data collected through observation, in-depth interviews, and documentation, and analyzed using George C. Edwards III’s policy implementation theory. The findings indicate that child protection implementation has not been fully optimized; ta’zir practices still include mild physical punishments that are not entirely aligned with child protection principles. In terms of communication, socialization of Law Number 35 of 2014 has not been conducted systematically. Regarding resources, training on child-friendly education remains severely limited. In terms of disposition, inconsistencies in attitude among staff were identified. Regarding bureaucratic structure, no written standard operating procedures exist. Supporting factors include leadership commitment and parental trust, while primary inhibiting factors include strong cultural traditions and limited human resource capacity. This study concludes that the pesantren remains in an adaptive stage and requires systemic strengthening in child protection implementation.